Intermittent Hypoxia Is Associated With High Hypoxia Inducible Factor-1α but Not High Vascular Endothelial Growth Factor Cell Expression in Tumors of Cutaneous Melanoma Patients - Almendros, Isaac; Martínez-García, Miguel Ángel; Campos-Rodríguez, Francisco; Riveiro-Falkenbach, Erica; Rodríguez-Peralto, José L.; Nagore, Eduardo; Martorell-Calatayud, Antonio; Hernández Blasco, Luis; Bañuls Roca, Jose; Chiner Vives, Eusebi; Sánchez-de-la-Torre, Alicia; Abad-Capa, Jorge; et al. (Frontiers in Neurology, 2018)
Epidemiological associations linking between obstructive sleep apnea and poorer solid malignant tumor outcomes have recently emerged. Putative pathways proposed to explain these associations have included enhanced HIF-1α and VEGF cell expression in the tumor and altered immune functions via intermittent hypoxia (IH). Here, we examined relationships between HIF-1α and VEGF expression and nocturnal IH in cutaneous melanoma (CM) tumor samples. Prospectively recruited patients with CM tumor samples were included and underwent overnight polygraphy. General clinical features, apnea-hypopnea index (AHI), desaturation index (DI4%), and CM characteristics were recorded. Histochemical assessments of VEGF and HIF-1α were performed, and the percentage of positive cells (0,<25%,25-50%,51-75%,>75%) was blindly tabulated for VEGF expression, and as 0, 0-5.9%,6.0-10.0%,>10.0% for HIF-1α expression, respectively. Cases with HIF-1α expression >6% (high expression) were compared with those <6%, and VEGF expression >75% of cells was compared with those with <75%. 376 patients were included. High expression of VEGF and HIF-1α were seen in 88.8% and 4.2% of samples, respectively. High expression of VEGF was only associated with increasing age. However, high expression of HIF-1α was significantly associated with age, Breslow index, AHI and DI4%. Logistic regression showed that DI4% (OR 1.03 [95%CI: 1.01-1.06]) and Breslow index (OR 1.28 [95%CI: 1.18-1.46]), but not AHI, remained independently associated with the presence of high HIF-1α expression. Thus, IH emerges as an independent risk factor for higher HIF-1α expression in CM tumors, and is inferentially linked to worse clinical CM prognostic indicators.